“Security Union” and the digital sphere: unpacking securitization processes - Fernandes, Sandra (2018)
Since 2016, the EU is boosting its agenda on security in a geopolitical context that comprises multiple challenges, namely the fight against terrorism, the migration pressure, relations with Russia, Brexit, and the redefinition of the Euro-Atlantic partnership. This article exposes drivers of the EU’s perspective on security, in particular, in the context of the “Security Union” framework and the emergence of the digital sphere as a defence matter.